The Mechanics of Distance Running - Dlugos, A.
· Experts believe that in order to optimal performance, a runner must run efficiently. According to Adrian and Cooper (1995), in order for a runner to be running efficiently, the runner must have their weight, build, strength, and flexibility all coordinated. Efficient running also depends on the coordination of the runner`s stride length, knee lift, foot placement, trunk and body posture, arm action, the rising and lowering of the runner`s center of gravity, and the effects of air resistance. Once the runner coordinates all these movements and applies the proper mechanical principles, his/ her running efficiency will (most likely) increase. · A runner exerting maximum effort can swing his/her leg forward much faster and greatly increasing his/her running speed. This is very important because the duration of forward swing of leg may be a limiting factor on the runner`s total speed (Luttgens and Hamilton 1997.) This is allows for the backward speed of the runner to be at least equal to his/her forward speed (Adrian and Cooper 1995.) . By eliminating forward and downward swing of legs and feet immediately prior to touchdown, the runner is allowing the feet to be placed in almost a straight line, directly under the runner`s center of gravity (Bunn---.) · Efficient running depends on a high knee lift. This delays placing the foot on the ground and provides clearance for swinging leg to reach full extension because of the lower position of the runner`s pelvis (Luttgens and Hamilton 1997.) The information that I gathered throughout this study can be used for many purposes. The first and probably most obvious one would be for elite runners and Olympic athletes. One change from an inefficient mechanical principle to a more efficient one could possibly cause the runner to subtract a second off his/her performance and may mean the runner receiving a gold medal instead of a silver. One could also use this as a teacher to help students learn and become efficient in their running at a young age. This efficiency can help them in the activities throughout their day. Researchers can also use this information to help study or create more mechanically efficient artificial limbs that may allow a person to walk again.